Aromaticity. XI. The Use of D Index in the Characterization of Antiaromatic Compounds. The Case of Fullerene - D`Auria, Maurizio (Letters in Organic Chemistry, 2016)
DFT calculations (B3LYP/6-311G+(d,p)) on antiaromatic compounds showed that these compounds are characterized by the presence of nonoccupied bonding π orbitals. The D index cne be used to characterize this type of compounds. The correlations between D and NICS for some pentalene derivatives have been examined. The aromaticity of antiaromatic pentalene in the excited triplet state has been discussed. The aromaticity of fullerene and of some other bowl-shaped molecules has been examined.
Keywords: fullerene